Memory B-Cell Responses Against Merozoite Antigens After Acute Plasmodium falciparum Malaria, Assessed Over One Year Using a Novel Multiplexed FluoroSpot Assay - Jahnmatz, Peter; Sundling, Christopher; Yman, Victor; Widman, Linnea; Asghar, Muhammad; Sondén, Klara; Stenström, Christine; Smedman, Christian; Ndungu, Francis; Ahlborg, Niklas; Färnert, Anna (Frontiers in Immunology, 2021)
Memory B cells (MBCs) are believed to be important for the maintenance of immunity to malaria, and these cells need to be explored in the context of different parasite antigens and their breadth and kinetics after natural infections. However, frequencies of antigen-specific MBCs are low in peripheral blood, limiting the number of antigens that can be studied, especially when small blood volumes are available. Here, we developed a multiplexed reversed B-cell FluoroSpot assay capable of simultaneously detecting MBCs specific for the four Plasmodium falciparum blood-stage antigens, MSP-119, MSP-2, MSP-3 and AMA-1. We used the assay to study the kinetics of the MBC response after an acute episode of malaria and up to one year following treatment in travelers returning to Sweden from sub-Saharan Africa. We show that the FluoroSpot assay can detect MBC to all four merozoite antigens in the same well, and that the breadth and kinetics varied between individuals. We further found that individuals experiencing a primary infection could mount and maintain parasite-specific MBCs to a similar extent as previously exposed adults, already after a single infection. We conclude that the multiplexed B-cell FluoroSpot is a powerful tool for assessing antigen-specific MBC responses to several antigens simultaneously, and that the kinetics of MBC responses against merozoite surface antigens differ over the course of one year. These findings contribute to the understanding of acquisition and maintenance of immune responses to malaria.